2018
DOI: 10.1039/c8cc01627e
|View full text |Cite
|
Sign up to set email alerts
|

Impact of partial interpenetration in a hybrid ultramicroporous material on C2H2/C2H4separation performance

Abstract: Phases of a 2-fold pcu hybrid ultramicroporous material (HUM), SIFSIX-14-Cu-i, exhibiting 99%, 93%, 89%, and 70% partial interpenetration have been obtained. 1 : 99 C2H2/C2H4 gas separation studies reveal that as the proportion of interpenetrated component decreases, so does the separation performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 62 publications
0
21
0
Order By: Relevance
“…Although the transient breakthrough simulation implies a slower C 2 H 2 breakthrough in UTSA-200a than in ZUL-200, the experimental C 2 H 2 uptake in breakthrough tests of UTSA-200a determined by two independent groups is notably smaller than the simulation value (Fig. S41) 30,32 . The purity of C 2 H 4 in the outlet effluent was analyzed to be >99.9999% with the C 2 H 2 concentration less than 1 ppm, which satisfies the quality standards of polymerization grade C 2 H 4 (C 2 H 4 > 99.95%, C 2 H 2 < 5 ppm) 49,50 .…”
Section: Synthesismentioning
confidence: 77%
See 1 more Smart Citation
“…Although the transient breakthrough simulation implies a slower C 2 H 2 breakthrough in UTSA-200a than in ZUL-200, the experimental C 2 H 2 uptake in breakthrough tests of UTSA-200a determined by two independent groups is notably smaller than the simulation value (Fig. S41) 30,32 . The purity of C 2 H 4 in the outlet effluent was analyzed to be >99.9999% with the C 2 H 2 concentration less than 1 ppm, which satisfies the quality standards of polymerization grade C 2 H 4 (C 2 H 4 > 99.95%, C 2 H 2 < 5 ppm) 49,50 .…”
Section: Synthesismentioning
confidence: 77%
“…For example, in industrial processes for producing polymer-grade ethylene (C 2 H 4 ), the design of efficient porous materials for acetylene (C 2 H 2 ) separation is the key to replacing solvent absorption and catalytic hydrogenation technologies. The leading materials in capturing trace C 2 H 2 from C 2 H 4 , including the NKMOF-1-Ni (Cu[Ni(pdt) 2 ])) 26 and the SIFSIX family [27][28][29] , all have a 3D coordination network structure that affords a high affinity for C 2 H 2 (Table S13), but the separation performance still needs improvement in view of the limited productivity of high-purity C 2 H 4 , and the material with benchmark C 2 H 4 productivity was reported to be unstable to water and even laboratory atmosphere [30][31][32] .…”
mentioning
confidence: 99%
“…NbOFFIVE-1-Ni is a fluorinated porous HUM and is typically derived from the SIFSIX family by ridging Ni(II)-pyrazine square grid layers with the (NbOF 5 ) −2 pillars 12,24 . In short, adequate amounts of hydrofluoric acid, pyrazine, niobium (V) oxide and nickel hexahydrate were mixed with 3 ml of deionized water in a 40 ml Teflon bomb.…”
Section: Sorbent Synthesismentioning
confidence: 99%
“…Such properties are significant in the understanding of the interactions and separation applications of such materials amongst other properties such as the chemical structure. Accordingly, a large number of studies reported on the control of the porous structure of such sorbents via different synthesis routes, physical and chemical alterations of the structure 21,22,24,30,31 . Figure 6(a) shows indicated a type I IUPAC classification indicating a dominant microporous structure 32 compared to a classical IV shaped isotherm for the SBA-15 sorbent.…”
Section: Ftir Ftir Spectroscopy Assists In Understanding the Interacmentioning
confidence: 99%
“…Our aim with MPMC and MCMD is to leverage the best hardware available to date, increase the physical accuracy of traditional force field modeling through the inclusion of explicit, long‐range many‐body polarization in both the energetics and forces. We have used both codes in many published theoretical studies but have not formally introduced them until now.…”
Section: Introductionmentioning
confidence: 99%